A sustentabilidade ambiental da agropecuária brasileira: Impactos, políticas públicas e desafios - Regina Helena Rosa Sambuichi; Michel Ângelo Constantino de Oliveira; Ana Paula Moreira da Silva; Gustavo Luedemann (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This study aimed to discuss environmental sustainability issues of the Brazilian agricultural sector, regarding aspects such as the impacts of the sector's growth on the natural environment, current policies and strategies needed to mitigate these impacts. Historically, agricultural policies implemented in Brazil did not consider the potential negative impacts of the development model adopted, leading to an imbalance in the tripod of sustainability by favoring the economic aspect at the expense of social and environmental. Only very recently, policy makers began to pay attention to agricultural sector sustainability issues and establish policies with this purpose. The challenge of developing a sustainable agricultural production, however, will require the adoption of multiple strategies such as the generation and diffusion of environmentally sound technologies, structuring of integrated agrienvironmental information systems and application of economic instruments that can minimize the negative externalities of the sector.
Keywords: Q1; Q15; 330; sustainable development; environmental sustainability; agricultural policy; agro-environmental policies; Nachhaltige Entwicklung; Landwirtschaft; Agrarpolitik; Brasilien